Motivation factors to involve in sports volunteer among students: the case of University of Malaya (UM) / Amira Diyana Hidzir ... [et al.] - Hidzir, Amira Diyana; Lamat, Siti Aida; Dahlan, Nur Dalilah; A. Rahman, Muhammad Wafi; Bakri, Nur Hani Syazwani (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Volunteers are a vital human resource at any sporting event, and numerous experiments have been undertaken to clarify the motivation factors of volunteers in multiple situations. Although numerous studies have identified various volunteer motivational factors on human service in general, little study has attempted to conducted volunteer motivational study at sporting events. The purpose of this study is to identify the main factor that motivates students in joining sports volunteer activity and to identify the different factors between the gender that motivate them to take part in sports volunteer activity. The research data were gathered from 496 students of the University of Malaya (UM) who are directly been involved in sports volunteer activity by using the Volunteer Motivation Scale for Sporting Event (VMS-ISE) with a total of 29 items from seven factors: expression of value, patriotism, career orientation, interpersonal contact, personal growth, extrinsic reward and love of sport. The result showed that the most respondent were female students (58.5%) compared to male students (41.5%). Students revealed that expression of values is the factor that better predicted the level of voluntary motivation (M= 6.34) and the lowest (M=5.41) goes to the factor of extrinsic reward. The Mann-Whitney analysis is used to identify motivation factors to be involved in sports activity between gender. The results also indicated that gender had significant effect with a p-value is p<0.05 is the factors of love of sport, extrinsic reward, expression of value, and career orientation. The theoretical and functional effects of these studies are discussed in more detail. The implication not only benefits to the volunteer itself but also towards volunteer organizations will next have a better management process as this research gives additional knowledge for them to plan, organize, lead and control the sport volunteer event appropriately.